Significant lattice-distortion effect on compressive deformation in Mo-added CoCrFeNi-based high-entropy alloys - Li, Jiaxiang; Yamanaka, Kenta; Chiba, Akihiko (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
Large lattice distortion is an essential feature of high-entropy alloys (HEAs). Herein, the deformation behaviors of three types of as-cast CoCrFeNi-based HEAs, which contained 0, 7.9, and 17.1 wt% Mo, were comparatively studied through compressive tests and microstructural observations. The intrinsic lattice distortion increased mainly as a function of the Mo content. By virtue of both the local strain incompatibility inside the coarse columnar grains of the as-cast microstructures and low dislocation mobility in HEAs, domain rotations were induced at low strains. Meanwhile, simple shear occurred between domains and produced a new boundary network in the microstructure. The large lattice distortion of the high-Mo HEA (17.1 wt%) gave rise to intense planar slip bands, on which a large number of dislocations slipped and impinged on strain-induced boundaries. As a result of the high back-stress hardening, the high-Mo HEA exhibited enhanced strain-hardening. At high strains, the stress concentration events increased as the lattice distortion of the HEAs increased; this promoted twin growth in the high-Mo HEA. The high-Mo HEA was highlighted with a high strain-hardening rate over a wide strain range. In this study, high-strength as-cast HEAs were developed based on the utilization of the lattice-distortion effect.